Back Cover: Next‐Generation Polymer Shells for Inorganic Nanoparticles are Highly Compact, Ultra‐Dense, and Long‐Lasting Cyclic Brushes (Angew. Chem. Int. Ed. 16/2017). Issue 16 (16th March 2017) - Morgese, Giulia; Shirmardi Shaghasemi, Behzad; Causin, Valerio; Zenobi‐Wong, Marcy; Ramakrishna, Shivaprakash N.; Reimhult, Erik; Benetti, Edmondo M.
Abstract : Next‐generation shells for inorganic nanoparticles (NPs) are polymeric "shields" designed to last. In their Communication onpage 4507 ff., E. M. Benetti et al. have demonstrated that when cyclic polymer ligands are grafted onto inorganic NPs, ultra‐dense and highly compact brush shells are generated. Core‐cyclic shell NPs are significantly more stable than their linear brush‐functionalized counterparts and show full bio‐inertness towards serum proteins.